'Kant our Contemporary'? Kitcher on the Fruitfulness of Kant's Theory of the Cognitive Subject. Issue 1 (31st January 2014) - Sturm, Thomas
Abstract In chapter 15 of Kant's Thinker, Patricia Kitcher claims that we can treat Kant as 'our contemporary', and that his theory of apperception 'offers "new" and plausible perspectives on issues of considerable recent interest'. I question this with respect to two of her four chosen topics. First, I address her attempt to show that Kant's theory of apperceptive self-knowledge is immune to sceptical doubts of the sort Barry Stroud presents. Second, I turn to her argument that this theory is superior to current accounts of the special authority of self-knowledge. Over and above specific weaknesses, it seems that Kitcher's considerations generally lack sufficient reflection on how philosophical arguments of the past can be relevant to current agendas.